The Swedish budget: for the fiscal year 1964/65 - Sweden (Stockholm : Ministry of Foreign Affairs , Ministry of Finance ., 1962)
This third edition of "The Swedish budget" contains information about the Government Budget 1964/65, with more detailed reviews of the main items of Government expenditure. The Budget Statement and the Economic Survey are presented in abridged versions.
"A summary"
rpm 20/02/2019
Ref
Keywords: Budget; Budget; Economic history; Sweden; Sweden